Population growth and its impact on water consumption in city of Ajdabiya (Albayan Scientific Journal, 2023)
This research aims to study one of the most important contemporary problems,which  is the  problrm of lack of electric power due to the inerease  in the population in the city of Ajdabiya during the period |( 1984 – 2022 AD) , as the city,s population increased from 59,235 people in 1984AD to about 143214 people in 2022AD, an increase of 83.979 people, which resulted in a shortage in the quantities of electricity supplied to the city, Because of the increase in per capita consumption of electrin enegy in the city, which in 2006 reached about 5845 kilowatt-hours, compared to the per capita share in the country, which amounted to 3347 kwh, And the per capita share continued to increase, especially in recent years, as the per capita share reached (5845)kilowatt-hours, in 2006 and 2022 respectively .
Keywords: Populaton growth; electricity; Per capita; Ajdabiya City